2014
DOI: 10.1371/journal.pone.0085482
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects from Clenbuterol and Ractopamine on Nematode Caenorhabditis elegans and the Underlying Mechanism

Abstract: In the present study, we used Caenorhabditis elegans assay system to investigate in vivo toxicity from clentuberol and ractopamine and the possible underlying mechanism. Both acute and prolonged exposures to clentuberol or ractopamine decreased brood size and locomotion behavior, and induced intestinal autofluorescence and reactive oxygen species (ROS) production. Although acute exposure to the examined concentrations of clentuberol or ractopamine did not induce lethality, prolonged exposure to 10 µg/L of clen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 63 publications
(84 reference statements)
1
29
0
Order By: Relevance
“…Taken together, the pro-oxidative effect of clenbuterol could be related to the metabolites formed during the 72-h treatment. These results are in accordance with those of Zhuang et al (2014), although it should be mentioned that the latter authors conducted their experiments on nematodes in vivo.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Taken together, the pro-oxidative effect of clenbuterol could be related to the metabolites formed during the 72-h treatment. These results are in accordance with those of Zhuang et al (2014), although it should be mentioned that the latter authors conducted their experiments on nematodes in vivo.…”
Section: Resultssupporting
confidence: 91%
“…Data on clenbuterol's pro-oxidative powers are scarce. Zhuang et al (2014) reported that acute exposure to clenbuterol applied in concentrations of 0.01-0.1 ng/ml, as well as a prolonged exposure to the same substance applied in concentrations of 0.01-0.1 ng/ml, did not induce significant intestinal autofluorescence in nematodes. Contrary, acute exposure to 5 ng/ml clenbuterol caused significant auto-fluorescence.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The methods were performed as described previously (Wu et al, 2014b;Zhuang et al, 2014). Nematodes were judged to be dead if they did not respond to a stimulus using a small metal wire.…”
Section: Lethality Growth Reproduction and Locomotion Behavior Assaysmentioning
confidence: 99%
“…Epoxiconazole was dissolved in DMSO (Sigma-Aldrich, St. Louis, MO, USA) and M9 buffer (2.5 g of NaCl, 3.0 g of Na 2 HPO 4 and 1.5 g of KH 2 PO 4 ) to prepare the working solution at final concentrations of 0.1, 1.0 and 10.0 μg/L. Epoxiconazole exposures were performed for 48 h in 24-well culture plates at 20 °C according to a previous description [24]. The solvent controls were prepared in the same way.…”
Section: Methodsmentioning
confidence: 99%